Navigating Cross-Cultural Business Strategies: The Impact of Globalization on International Market Entry in Emerging Economies - Vina Apriliani Su’udiah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to explore cross-cultural business strategies within the context of globalization, focusing on the challenges faced by companies entering emerging markets. The research seeks to identify key cultural factors—such as local values, consumer behavior, and business practices—that influence companies' market entry strategies and decision-making processes. A qualitative approach with a phenomenological design was employed to gain in-depth insights into the experiences of business executives, managers, and cultural consultants engaged in cross-cultural strategies within multinational companies. Using purposive sampling, participants included executives, international economic researchers, strategy consultants, and cross-cultural experts with direct experience in market entry strategies for emerging economies. Data were collected through semi-structured, in-depth interviews, and thematic analysis was applied to interpret the findings. The results reveal that companies able to adapt their products, marketing strategies, and operations to align with local cultural norms experience higher consumer engagement and market acceptance. The findings underscore the importance of cultural intelligence as a critical competency for international business success, as companies with strong cultural awareness are better positioned to navigate the complexities of diverse and rapidly evolving global markets.